Effect of CaO nanocatalyst on bio-oil production from algae and date seeds via microwave-assisted co-pyrolysis - Al Dulaimi, Mustafa; Al Oqaili, Firas; Al-anssari, Sarmad; Kadhum, Abdul Amir H.; Hamzah, Husam Talib; Sridevi, Veluru; Abdullah, Thamer Adnan; Abdullah, Oday (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
One of the most effective ways of managing solid waste is microwave-assisted pyrolysis. This research used MW-assisted catalytic co-pyrolysis to extract essential oils from algae powder (AP) and date seed (DS). Graphite and a CaO nanocatalyst were utilized. As for the feedstock, it was a 1:1 mixture of AP and DS. The char content, oil production, and gas generation of co-pyrolysis yields varied between 18.8 wt% and 24.31 wt%, 43.08 wt%, and 55.295 wt%, and 25.905% to 32.60 wt%, respectively. The effect of the CaO nanocatalyst on product yields, feedstock conversion, and heating rates was analyzed. Product yields, average heating rates, and conversion factors were among the metrics studied to determine the synergistic effects and pyrolysis index, which represent the effect of materials composition when mixed to improve the thermal decomposition products and the efficiency of the process. More oil and char were produced due to the synergy that occurred during co-pyrolysis. The bio-oil obtained from algae powder (AP) co-pyrolysis and date seed (DS) was analyzed using GC-MS. The catalyst allowed for the synthesis of aliphatic compounds, aromatic compounds, amides, and alkenes by co-pyrolysis synergy. The significance of this work lies in its demonstration of an efficient and sustainable method for converting algae and date seeds into valuable bio-oil using catalytic microwave-assisted pyrolysis, highlighting the increased yield, product quality, and process efficiency through synergistic interactions.